Surface Water Pollution in Lagos, Nigeria - Emakpor, Oluwaseyi Amos; Suenu, Adebowale Adeyemi -; Salami, Wale; Odunbaku, James Bamidele (NIU Journal of Social Sciences, 2025)
Surface water is one of the most vulnerable in terms of pollution in Lagos State. The risks of surface water were high in many areas of the state because of polluted activities on the water bodies. And this has reduced the quality of surface water and made it unfit for human use. The primary data for the study was collected through direct oral interviews of 25 residents of the state through random sampling technique. It also involved the use of secondary data like textbooks, newspapers and journals.  This paper focused on the causes of surface water pollution in Lagos State Nigeria, which include, industrial wastewater, agricultural effluence, sawdust seepage, direct flush of septic tanks into the seas and commercial sand dredging. The research therefore concluded that revocation of hazardous activities around surface water in Lagos State such as, open defecation, commercial sand dredging and relocation of sawmills to area that could contain them without causing problems to the surface water will preserve the quality of surface water in the state. Keywords: Lagos State, Sand dredging, Sawdust seepage, Sustainable development Surface water, Water Pollution.